USING PICTURE STRIP STORY IN TEACHING SPEAKING SKILL - MUKMIN MUKMIN (JURNAL PENDIDIKAN GLASSER, 2021)
This research is aimed to find out whether students’ speaking skill can be increased by using picture strip story or not. This research employed pre-experimental design. The variables of this research were the picture strip story as the independent variable and the students’ speaking skill as the dependent variable. The population of this research was the XI grade of SMK Daerah Luwuk which consists of thirteen students. The technique sampling was total sampling, which means that all population was taken as the sample of this research. The researcher use test as the main instrument in this research which is divided into pre-test and post-test. The data analysis of this research used was statistic calculation. The result of the research, the mean score of pre-test was 67.76 while the mean score in post-test was 75.73 and the testing hypothesis, the t-counted score was 5.533, while t-table for degree of freedom 12 and the level of significance = 0.05 was 1.782. It indicated that the hypothesis was accepted because picture strip story had increased the students’ speaking skill.